The development of agriculture and forestry in the tropics : patterns, problems, and promise - Phillips, John Frederick Vicars (London, Faber and Faber, 1961)
The book draws together, a broad classification of the patterns, the problems and the promise of agriculture and forestry in the tropics.
Includes bibliographical references.
lje
Loans
Keywords: Agriculture; Forests and forestry; Tropics